2021
DOI: 10.7150/jca.46282
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Survivin in Nasopharyngeal Carcinoma: A Systematic Review and Meta-analysis

Abstract: Background: Previous studies have shown that survivin has potential prognostic value in nasopharyngeal carcinoma. However, the results remained controversial until now. Thus, to investigate the influence of survivin expression on prognosis and clinical characteristics in nasopharyngeal carcinoma, we performed this meta-analysis. Methods: We searched PubMed, PMC, Embase, Web of Science, Cochrane Library, and China National Knowledge Infrastructure electronic databases from their establishment to 1 March 2021. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Pharmaceutical inhibition of survivin, or reduction of survivin protein level, suppressed metastasis of breast 25 , ovarian 26 , and lung cancer 27 . Moreover, the high protein level of survivin is corrected with the poor prognosis of HNSCC and NPC [28][29][30] . Our data revealed that survivin depletion blunted the malignant phenotype of NPC cells, including the inhibitory effects on cell viability, colony formation, and in vivo tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmaceutical inhibition of survivin, or reduction of survivin protein level, suppressed metastasis of breast 25 , ovarian 26 , and lung cancer 27 . Moreover, the high protein level of survivin is corrected with the poor prognosis of HNSCC and NPC [28][29][30] . Our data revealed that survivin depletion blunted the malignant phenotype of NPC cells, including the inhibitory effects on cell viability, colony formation, and in vivo tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Butein suppresses osteosarcoma 19 , cervical cancer 20 , 21 , colorectal cancer 22 , hepatocellular carcinoma 23 , breast cancer 24 , 25 , lung cancer 26 , and oral squamous cell carcinoma 27 . The mechanism studies have identified multiple intracellular targets of Butein, including AurkB, mTOR, NF-κB, EGFR, and c-Met 17 , 28 30 . Butein induces cell cycle arrest, promotes apoptosis, suppresses angiogenesis/metastasis, and compromises glycolysis 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of Survivin contributes to cell cycle progression and apoptosis dysregulation, which is correlated with tumorigenesis in NPC [24][25][26]. Survivin is conducive to maintaining EBV genomes in EBV-positive Burkitt lymphoma cells [27] and is used as a biomarker to predict the malignancy of NPC [28,29]. Therefore, targeting survivin is a promising strategy for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%